If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 495 = 19 + -17n Solving 495 = 19 + -17n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '17n' to each side of the equation. 495 + 17n = 19 + -17n + 17n Combine like terms: -17n + 17n = 0 495 + 17n = 19 + 0 495 + 17n = 19 Add '-495' to each side of the equation. 495 + -495 + 17n = 19 + -495 Combine like terms: 495 + -495 = 0 0 + 17n = 19 + -495 17n = 19 + -495 Combine like terms: 19 + -495 = -476 17n = -476 Divide each side by '17'. n = -28 Simplifying n = -28
| 5x+43x^2=0 | | 4-8/3x=19 | | 3/4*x-7=14 | | a^2+3a-44=0 | | fm=a | | am=f | | ma=f | | 2=11+n/4 | | 11-4*x/5=19 | | 2*x/3+15=17 | | 1/4*x-15=-7 | | k/5+9=11 | | 21+24y=y | | 23-14w=3-4w | | 4-1/7*x=13 | | y-4x=48 | | 1/4*x+5=15 | | 5m-6-2m=3 | | 4(3x-8)-(2x-7)+5x= | | 13x-23=39 | | -319=-20a+1 | | -3(4-x)=4(2x+1) | | -7/5x=-2 | | 3y+4/10=y/5 | | x=7(-x+4)/3 | | f(-1)=x^2+4x-6 | | -(2-x)+3(6-8x)+12= | | 13x-23=15 | | 24y+24=y | | -8/5x=-1 | | 5n+1+76=12n | | -9(6+u)+2u=-10 |